Pengaruh Pola Asuh Otoriter Orang Tua dan Kontrol Diri terhadap Perilaku Agresif Siswa pada Lingkungan Sekolah - Viska Dea Nopiana; Puspa Rahayu Utami Rahman; Yulyanti Minarsih (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Aggressive behavior in adolescents is one of the problems that often arise in the school environment and can be influenced by several factors, including parenting styles and individual self-control abilities. This study aims to determine the effect of parental authoritarian parenting and self-control students ‘aggressive behavior. This study uses a quantitative approach with a causality method. The research respondents were 279 students of grades 10 dan 11 of SMKN 2 Karawang using 3 scales, namely the Parental Authority Questionnaire (PAQ), Brief Self-Control Scale (BSCS), AND The Aggression Questionnaire as a data collection tool. The result of this study indicate that maternal authoritarian parenting significantly influences aggressive behavior, paternal authoritarian parenting significantly influences aggressive behavior, self-control significantly influences aggressive behavior, and maternal, parental authotitarian parenting and self control simultaneously influence aggressive behavior. Maternal, paternal, and self-control have an influence of 23,1 % on aggressive behavior, the remaining 76,9 % is likely explained by other factors not included in this study. The findings of this study provide a deeper understanding of how both maternal and paternal authoritarian parenting, as well as self-control, contribute to aggressive behavior. It is noteworthy that maternal and paternal authoritarian parenting independently have significant impacts on aggressive behavior, which suggests that both parents play an important role in shaping their children's emotional and behavioral responses. Additionally, the study reveals that self-control serves as a buffer, moderating the influence of parenting styles on aggression. The combined influence of these factors—parenting styles and self-control—accounts for 23.1% of the variance in aggressive behavior, indicating that other external or internal factors, such as peer influence, socio-economic background, or mental health, may also contribute to adolescent aggression.